The Role of JASTIP in E-Marketplace Adoption: A UTAUT Model Analysis with Gender as a Moderator in West Papua - Arniawati, Arniawati; Inan, Dedi Iskandar; Juita, Ratna`; Indra, Muhamad (ISB Atma Luhur, 2025)
E-marketplaces play a pivotal role in Indonesia’s digital economic transformation; however, infrastructural limitations, high logistical costs, and low levels of technological literacy hinder their adoption in West Papua Province. Jasa Titip (JASTIP) represents an informal digital facilitation mechanism that enables communities to collectively and affordably access e-marketplace products. Importance–Performance Map Analysis (IPMA) is used to identify strategic intervention priorities for e-marketplace adoption in West Papua using an expanded Unified Theory of Acceptance and Use of Technology (UTAUT) framework. The moderating influence of gender in community-based social support is examined. PLS-SEM was used to analyze data from 177 respondents. Results show that enabling environments, hedonic incentives, and social influence greatly affect behavioural intention and utilization. Gender also moderates social impact and behavioural intention, highlighting its function in adoption. The model explains 62.1% of behavioural intention and 66.2% of use behaviour. Policymakers and e-marketplace stakeholders should learn from these results about the necessity of inclusive initiatives that account for gender-specific adoption habits. Moreover, they highlight the critical role of JASTIP practices in overcoming structural barriers to digital access in underserved regions